The Potential of Ethanol Extract of Pasak Bumi Roots (Eurycoma longifolia Jack) as an Anti-Prostate Cancer In Vitro Against PC-3 Cells - Kania, Nia; Rahman, Eka Yudha; Priyandoko, Didik; Sabrina, Adilah Hafizha Nur; Widowati, Wahyu; Azis, Rizal; Annaba, Aziz; Hadiprasetyo, Dhanar Septyawan; Alexandro, Garry (Science and Technology Indonesia, 2025)
The prevalence of prostate cancer cases in men is expected to continue increase. In 2040, it is estimated that there will be 2.293.818 new cases and a 1.05% increase in the death rate due to prostate cancer. Eurycoma longifolia Jack roots extract (ELE) has potential as an alternative treatment. This study aims to analyze ELE potential as an anti-prostate cancer agent through in silico assay and in vitro assays on the prostate cancer cell line (PC-3). ELE compounds were docked against Casp-3, Casp-8, HAX-1, p27, and PTEN. In vitro assays on PC-3 cells were used, namely cell viability (WST-8), ROS levels; cell cycle; and cell apoptosis (flow cytometry), PC-3 cell senescence (μ-Galactosidase staining), Casp-3; Casp-8; HAX-1; p27; and PTEN gene expression (qRT-PCR). All proteins target were successfully docked with ELE compounds and presented binding interactions. ELE is known to reduce viability, intracellular ROS levels, live cells, necrosis, and reduce HAX-1 gene expression, and inhibit the cell cycle G0/G1 phase. ELE can also increase inhibition, senescence, late and early apoptosis, and Casp-3, Casp-8, p27, and PTEN gene expression. ELE 100 μg/mL is the most effective concentration. ELE has potential as an anti-prostate cancer agent through apoptosis, cell cycle, and antioxidant pathways